Mechanistic insight into the biomilling of goethite (alpha-FeO(OH)) nanorods using the yeast Saccharomyces cerevisiae - Sharan, Chandrashekhar; Khandelwal, Puneet; Poddar, Pankaj (RSC Advances, 2015)
Since the last decade, eco-friendly routes for the synthesis of nanostructured materials of various types and functionalities have been a topic of enormous interest in the field of nanotechnology. The primary work in this field started with the `bottom-up' microbial synthesis of nanoparticles, however, the bioleaching potential of microbes was initially overlooked in this research. The bioleaching process is useful especially where the synthesis of particles with size < 10 nm is challenging. In the present work, the mechanistic insight of biomilling for a gradual transformation of anisotropic alpha-FeO(OH) rod-shaped particles into isotropic nanoparticles below 10 nm size has been explored using detailed UV-vis spectroscopy, transmission electron microscopy, atomic force microscopy, X-ray diffraction, and X-ray photoelectron spectroscopic studies which suggest that the aquo group present at the alpha-FeO(OH) surface may provide the site for interaction with carboxyl ions of protein molecules which results in the formation of a stable coordination compound with Fe3+ ions. This will create a new Fe3+ ion on the surface of the lattice which leads to the repetition of the process of protein complexation with Fe3+ ions and dissociation of the complex from the lattice that causes the fragmentation of bigger nanoparticles into protein functionalized smaller nanoparticles.